2013
DOI: 10.1038/npp.2013.329
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Associated Changes in the Corticosterone Response to Acute Restraint Stress: Evidence for Increased Adrenal Sensitivity and Reduced Corticosterone Response Duration

Abstract: Exercise promotes stress resistance and is associated with reduced anxiety and reduced depression in both humans and in animal models. Despite the fact that dysfunction within the hypothalamic pituitary adrenal (HPA) axis is strongly linked to both anxiety and depressive disorders, the evidence is mixed as to how exercise alters the function of the HPA axis. Here we demonstrate that 4 weeks of voluntary wheel running was anxiolytic in C57BL/6J mice and resulted in a shorter time to peak corticosterone (CORT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 49 publications
(88 reference statements)
3
37
0
Order By: Relevance
“…Our study is in accordance with earlier reports on reduced adrenal responsiveness to ACTH [26] and impaired explicit memory [33] in marathon runners. While several studies showed an exaggerated response to CRH stimulation after pre-treatment with 1.5 mg DEX [15,16] , this study found the response to CRH after 3.0 mg DEX not to differ between runners and controls.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our study is in accordance with earlier reports on reduced adrenal responsiveness to ACTH [26] and impaired explicit memory [33] in marathon runners. While several studies showed an exaggerated response to CRH stimulation after pre-treatment with 1.5 mg DEX [15,16] , this study found the response to CRH after 3.0 mg DEX not to differ between runners and controls.…”
Section: Discussionsupporting
confidence: 94%
“…In mice, wheel running is associated with increased adrenal size but not with increased negative feedback through GR-mediated mechanisms. These findings suggest that exercise may promote stress resilience in part by ensuring a more rapid and shortened HPA response to a stressor, thereby affecting overall exposure to the potentially negative effects of more sustained HPA axis activation [26] .…”
Section: Discussionmentioning
confidence: 90%
“…This effect was most robust following restraint stress. Thus, elevated circulating levels of corticosterone and reduced general locomotion cannot explain the decrease in ethanol consumption since these effects resolved when ethanol was made available for consumption 4 h following the stress exposure (Cabib et al, 1988; Hare, Beierle, Toufexis, Hammack, & Falls, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…The rest of the groups were exposed to restraint stress (RS), social defeat (SD), or forced swim (FS) either 1 or 4 h before access to ethanol in their home cages for 5 consecutive days. These time intervals were chosen to evaluate ethanol intake near peak stress-induced physiological changes or at a more remote time point when the acute effects of stress, such as elevated corticosterone levels and reduced locomotor activity had subsided (Cabib, Kempf, Schleef, Mele, & Puglisi-Allegra, 1988; Hare, Beierle, Toufexis, Hammack, & Falls, 2014; Patchev & Patchev, 2006). The following week, all mice resumed ethanol intake without exposure to stress.…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptional changes in the striatum, a major component of the mesolimbic dopaminergic reward pathway, were examined in order to provide insight into the mechanisms underlying reduced ethanol preference. Wheel running in rodents has been shown to induce a myriad of behavioral responses related to tests of stress, anxiety, and depression (Adlard and Cotman, 2004; Brené et al, 2007; Clark et al, 2015; Dishman et al, 2006; Greenwood et al, 2011, 2013; Hare et al, 2014; Lapmanee et al, 2013; Loughridge et al, 2013; Mika et al, 2015; Sciolino et al, 2015; Sierakowiak et al, 2014). Furthermore, previous studies have demonstrated wheel running was sufficient to reduce voluntary intake of amphetamine (Kanarek et al, 1995), cocaine (Cosgrove et al, 2002; Smith et al, 2011), as well as nicotine-seeking during extinction (Sanchez et al, 2013; Smith and Lynch, 2011).…”
Section: Discussionmentioning
confidence: 99%